An item response theory analysis of the Olweus Bullying scale. Issue 1 (January 2015) - Breivik, Kyrre; Olweus, Dan
<x xml:space="preserve">Abstract</x> In the present article, we used IRT (graded response) modeling as a useful technology for a detailed and refined study of the psychometric properties of the various items of the Olweus Bullying scale and the scale itself. The sample consisted of a very large number of Norwegian 4th–10th grade students (n = 48 926). The IRT analyses revealed that the scale was essentially unidimensional and had excellent reliability in the upper ranges of the latent bullying tendency trait, as intended and desired. Gender DIF effects were identified with regard to girls' use of indirect bullying by social exclusion and boys' use of physical bullying by hitting and kicking but these effects were small and worked in opposite directions, having negligible effects at the scale level. Also scale scores adjusted for DIF effects differed very little from non‐adjusted scores. In conclusion, the empirical data were well characterized by the chosen IRT model and the Olweus Bullying scale was considered well suited for the conduct of fair and reliable comparisons involving different gender‐age groups. Information Aggr. Behav. 41:1–13, 2015. © 2014 Wiley Periodicals, Inc.